Resistensi Komunitas Keagamaan terhadap Partisipasi Media Sosial - Nessya Mayla Faiza; Utari Mutiara Ayu; Noerma Kurniwa Fajarwati (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Religious communities like Indonesia often discuss religious issues. Determining the Eid al-Adha holiday in 2022 is one of the issues that is receiving attention. As is known, the Indonesian government determines the Eid al-Adha holiday in two ways: rukyat and reckoning. On the Instagram account @kemenag_ri, the Ministry of Religion of the Republic of Indonesia held an Isbat Session Teleconference on June 29 2022, and the results showed that the date set on the calendar had to be changed from July 9 2022 to July 10 2022. Instagram users provided this decision directly. This shows that the religious community has participated and there is agreement in handling the results of the Isbat Session. As an effort to explore the interactions that exist within religious communities, this research uses netnography techniques.